Detection of land cover changes using remote sensing and geographical information system. - Hj. Mohd. Noor, Norzailawati; Nurul hidayah, Yahya (2012)
Rapid urbanization strains a country’s capacity to meet new urban developments, and the consequences brought serious losses of arable land, forest, transforming the spatial pattern of urban land uses worldwide and polluting water bodies. Urban expansions have not only increased the exploitation of natural resources but it has also changed the land cover patterns. The objective of this research is reviewing changes in land cover pattern using sensing imagery and GIS approach. Recently, land cover types can be directly derived from remotely sensed data, which provides a powerful way to monitor urban environment and human activities. The analysis of the satellite images using geographical information system (GIS) are often used to determine the changes in the land cover patterns. The finding of this paper demonstrates the usefulness of a remote sensing and GIS approach in detecting, monitoring and analyze the changes of land cover particularly in urban area. Finally, a discussion of the needs for further research is presented.